Negative Exposures : Knowing What Not to Know in Contemporary China - Hillenbrand, Margaret, 1972- (Book collections on Project MUSE., 2020)
"In NEGATIVE EXPOSURES Margaret Hillenbrand uses aesthetic forms to investigate the structuring force of the 'open secret' in Chinese governance and society. Traditional scholarship on China has offered two explanations for the lack of cultural memory around important historical events: government censorship of material, and the subsequent cultural amnesia that results from the lack of historical information. However, as Hillenbrand argues, these explanations eclipse another structuring force of Chinese governance and society: the open secret. In this book, Hillenbrand argues that much of what is not openly addressed in Chinese cultural discourse is neither censored nor forgotten; rather, it is known privately and disavowed publicly through a collective verbal silence. Yet, despite this silence, historical events remain; they linger as secret knowledge, not in official government records and archives, but in aesthetic forms, particularly in historic photographs. In this book, Hillenbrand theorizes the photo-form, a historical photograph that is manipulated and reworked in paint, ink, celluloid, fabric, or other artistic medium, to offer an explanation for how aesthetic forms constitute the core of open secrecy in Chinese culture. Photo-forms, argues Hillenbrand, achieve two cultural effects. First, they defamiliarize the familiar, offering slant views into the historical record-histories of violence, trauma, and political resistance. Second, on the level of the secret, they act as a type of initiation into public secrecy wherein the creation of the photo-form encodes the secret and the act of decipherment serves as an initiation of the viewer into the secret's knowledge. Through analyses of the photo-form in contemporary Chinese culture, NEGATIVE EXPOSURES intervenes in discourses of secrecy studies and conceptualizations of cryptocracies that overlook the social force of the open secret. This book is structured around case studies of three events in Chinese history-the Nanjing Massacre, the Cultural Revolution, and the Tiananmen protests-and the ways their histories live on as an open secret in contemporary Chinese society. In chapter 1 Hillenbrand examines photo-forms which rework the violent imagery of the Nanjing Massacre, paying specific attention to how these photo-forms are reworked into state propaganda aimed at eliciting a set of patriotic responses. Chapter 2 centers on family portraits taken during the Cultural Revolution, and how these photo-forms address taboos surrounding the violence enacted by everyday citizens during the Revolution. Chapter 3, also on the Cultural Revolution, focuses on one photograph in particular: the portrait of Bian Zhongyun, a vice principal at the Beijing Normal University, beaten to death by her Red Guard students. Hillenbrand argues that the circulation of this photo-form is meant to apply pressure on the larger public secret that many of China's top leaders are connected with Bian Zhongyun's death. Chapter 4 turns to the Tiananmen protests by way of the Tank Man photograph, and reveals how the reception of this photograph is split along generational lines. In the conclusion, Hillenbrand addresses how open secrecy works to serve deeply public needs. This book will be of interest to students and scholars of Sinophone studies, Asian studies, art and visual studies, cultural studies, and secrecy studies"--